AVACONS - Loret de Mola Caceres, Roberto Martin (2022)
Most of the companies in the real estate sector offer their housing projects at an early stage, that is, still in the design or construction phase, in order to provide better prices and locations. Faced with this situation, different problems arise such as the lack of monitoring of the main inventory management indicators in real estate companies or the time that buyers must invest to ensure adequate installation according to budget items, another of the main Problems identified include the lack or little communication between the representatives of the real estate companies and the clients, as well as the non-fulfillment of the commitments that the real estate companies acquire with the clients, the latter being the most affected by having no way of doing monitoring their investment, which, in turn, generates mistrust. This project proposes a multiplatform technological solution (mobile and web) which has been called AVACONS, which will allow real estate companies to connect with their clients so that the latter can observe and monitor the progress of the construction of your home and the entire real estate project through different types of content such as photos, videos and detailed reports of finishes, generating satisfaction, trust and loyalty in them. On the side of real estate companies, they will have better logistical traceability in controlling their construction progress, which will generate fewer delays and expenses in their construction projects. Likewise, they will achieve a competitive advantage through the proposed service through the recommendations that will be created from satisfied and loyal customers, making it possible to attract new users and therefore increasing sales relying on the reference of their customers supported with satisfaction and recommendation indicators.